PROFESSIONAL BURNOUT OF EMPLOYEES OF HIGHER EDUCATION INSTITUTIONS - Babanov, Sergey Anatolyevich; Daryukhina, Ekaterina Aleksandrovna; Lysova, Margarita Valerianovna; Babanov, Andrey Sergeevich; Glazistov, Anton Vladimirovich (Medicine in Kuzbass, 2026)
The article addresses the issue of professional burnout among university educators. A systematic literature review was conducted using data from Russian and foreign studies conducted between 2015 and 2025. The search strategy included the use of the following databases: eLIBRARY.RU, CyberLeninka, PubMed, Scopus, and Google Scholar. The search queries included the keywords «professional burnout», «university professors», «emotional exhaustion», «burnout diagnostics», and their variations. A total of 70 sources that met the search criteria were analyzed, and 36 were included in this study. Psychological and organizational factors influencing the development of burnout syndrome are highlighted, along with its consequences for the health and work efficiency of teachers. The importance of comprehensive diagnostics, including psychological questionnaires and medical methods, as well as the significance of risk forecasting and the development of preventive programs, is emphasized. Special attention is given to the impact of modern conditions such as digitalization and the COVID-19 pandemic on the intensification of emotional exhaustion among educators. The features of burnout in different types of universities (technical, humanitarian, medical) are analyzed, underscoring the need to adapt support measures according to the specifics of the educational environment. Conclusions are drawn about the necessity of integrating scientific, organizational, and practical approaches to preserve professional health and improve the quality of the educational process.